EVALUASI PENERAPAN KONSEP BIOKLIMATIK PADA RAD+AR HQ - Benno Tumpak Ahimsa Sirait; Yenny Gunawan (Riset Arsitektur (RISA), 2023)
Abstract - Bioclimatic architecture has existed since the 20th century, but its development in Indonesia has only recently been seen. Architecture in Indonesia often imitates or plagiarizes architecture in foreign countries with different climates. As a result, building created with such notions are uncomfortable for users and also wasteful of energy use. Indonesia's location in a tropical climate has not yet been widely developed for its application in present day architecture. This research begins by examining bioclimatic architecture in Jakarta and RAD+ar HQ building as the object of study with the concept of bioclimatic architecture. Furthermore, physical data collection, environmental condition measurement data, and perception interview data were carried out to conduct an assessment of how the application of the bioclimatic concept in RAD+ar HQ buildings and how building users' perceptions of comfort in RAD+ar HQ/ buildings were taken. From this study, it was found that the application of the bioclimatic concept to the RAD+ar HQ building was not fully due to the different initial concepts and modifications due to the limitations of the pandemic conditions, which concerned air circulation between users of the building. Most of the users of RAD+ar HQ buildings already feel comfortable thermally and visually, but not all users feel comfortable thermally, this can be caused by thermal conditions where the majority of the rooms are outside the standard of thermal comfort. Although bioclimatic principle was applied to the architecture, the bioclimatic principles have not been applied entirely. Key Words: bioclimatic architecture, tropical architecture, RAD+ar Headquarters